2005
DOI: 10.1152/ajprenal.00378.2004
|View full text |Cite
|
Sign up to set email alerts
|

Renal ischemia-reperfusion injury and adenosine 2A receptor-mediated tissue protection: role of macrophages

Abstract: The role of monocytes/macrophages in the pathogenesis of ischemia-reperfusion injury (IRI) is unknown. We sought to determine whether activation of macrophage adenosine 2A (A(2A)) receptors (A(2A)Rs) mediates tissue protection. We subjected C57Bl/6 mice infused with clodronate [dichloromethylene bisphosphonate (Cl(2)MBP)] to IRI (32 min of ischemia followed by 24 h of reperfusion) to deplete them of macrophages. IRI induced an elevation of plasma creatinine that was reduced with Cl(2)MBP (26% of control). Adop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
212
1
7

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(232 citation statements)
references
References 41 publications
12
212
1
7
Order By: Relevance
“…11 Several groups have shown that systemic depletion of phagocytes, including monocytes and macrophages, with liposomal clodronate before I/R decreases morphologic kidney damage and attenuates the increase in blood urea nitrogen (BUN) and creatinine. 11,12 These observations are consistent with the idea that macrophage infiltration augments the inflammatory response and promotes tubular injury. Recent studies in other forms of immune-mediated renal injury raise the possibility that it is the effector phenotype of the recruited macrophages rather than their presence alone that determines the extent of renal parenchymal injury.…”
supporting
confidence: 85%
“…11 Several groups have shown that systemic depletion of phagocytes, including monocytes and macrophages, with liposomal clodronate before I/R decreases morphologic kidney damage and attenuates the increase in blood urea nitrogen (BUN) and creatinine. 11,12 These observations are consistent with the idea that macrophage infiltration augments the inflammatory response and promotes tubular injury. Recent studies in other forms of immune-mediated renal injury raise the possibility that it is the effector phenotype of the recruited macrophages rather than their presence alone that determines the extent of renal parenchymal injury.…”
supporting
confidence: 85%
“…Renal IR injury is associated with the rapid accumulation of a massive number of neutrophils and monocyte/macrophages in the interstitium of injured kidney (3,22,25,27). Animal studies have shown that macrophage depletion in the mouse or rat attenuates renal IR injury, while adoptive macrophage transfer into these animals reconstitutes renal IR injury (14,22), supporting the important role of macrophages in renal IR injury. Whether PKG has an effect on an innate immune response and kidney inflammation in renal IR injury is not known.…”
Section: Discussionmentioning
confidence: 96%
“…The functional role of DCs in AKI has been examined using liposomal clodronate. 3,56 In ischemic AKI, clodronate reduced the severity of renal injury, 31,57 whereas in the cisplatin model, clodronate did not affect renal injury. 56 Unfortunately, clodronate is not specific for DCs, which limits the interpretation of these results.…”
Section: Discussionmentioning
confidence: 99%